The return of the king : being the third part of The lord of the rings - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. Lord of the rings, 1994)
While the evil might of the Dark Lord Sauron swarmed out to conquer all Middle-earth, Frodo and Sam struggled deep into Mordor, seat of Sauron's power. To defeat the Dark Lord, the accursed Ring of Power had to be destroyed in the fires of Mount Doom, but the way was impossibly hard and Frodo was weakening. Weighed down by the compulsion of the Ring, he began finally to despair.